Al-‘Ijaz al-Raqmiy fī al-Qur’an al-Karim ‘inda ‘Abdul Dāim al-Kaḥīl - Asif Trisnani; Dinka Wijayanti (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2018)
This paper discusses about the miracles of number in al-Qur’an in accordance to ‘Abdu ad-daim al-Kahil. These miracles are for the example: balāghiy, tasyri’iy, lughawiy, ṭibbiy, and still there are many other kind of miracles in the verses of al-Qur’an. Miracle of number in Qur’an, however, is the new one. Much of theologian says that the miracle of al-Qur’an comes from balāghiy, tasyri’iy, lughawiy, and not from the side of number. In this article, writer indents to express miracle of number in al-Qur’an more. Precisely, it is a mediator to look at the miracle of al-Qur’an along to prove its authenticity to all who question it. In the case of dialogue, we can accord it to not Muslim fellows that al-qur’an is an outstanding miracle in the world. This paper concludes there are seven numbers in al-Qur’an coordinated with calculation of text, message, sentence and letter in al-Qur’an. It is also explained that number in Qur’an embraces kind of harmony such as balāghah. Finally, according to Abdu al-Daim al-Kahil, number is a landmark for the legacy of Islam.